Digital Health Model for South Africa’s National Health Insurance: Addressing Hospital Occupancy and Emergency Care - Moonsamy, Wesley; Singh, Shawren (Journal of Health Informatics in Africa, 2024)
Background and Purpose: South Africa will be unifying the current fragmented healthcare system by implementing the National Health Insurance. This poses inevitable challenges to the associated information systems. This research introduces the need for an information systems model to support the Federated Health Information Architecture proposed by the Department of Health. Methods: The Health Normative Standards Framework documentation was studied in conjunction with the Life Esidimeni Health Ombud report to determine gaps in the proposed architecture. Results: Five gaps were identified during this research (the view of shared Electronic Health Records (EHR) is oversimplified, key decision makers are not included in the list of stakeholders, emergency services is not adequately supported, medical aid schemes are not included, mature architectural standards need to be developed) and it was determined that a digital health systems model needs to be developed to support the current architecture to assist with resolving some of the identified gaps. Conclusions: Data synchronisation issues are inevitable with a large project such as the NHI. To minimise mistakes, fewer assumptions regarding the interoperability of systems need to be made. The proposed architecture as it stands may not cater to the needs of the NHI. A new model that can support the NHI especially within emergency care and hospital occupancy monitoring needs to be created.